IgA antibodies in the diagnosis of acute schistosomiais mansoni - Kanamura, Herminia Yohko (1991)
Specific IgA and IgM antibodies to a polysaccharide antigen present in the epithelial ceIls of the schistosome gut were measured by an indirect immunofluorescence technique, using paraffin sections of adult worms fixed in Rossman's fixative. Sera from 40 schistosomiasis patients, 20 acute and 20 with chronic form, and also from 40 individuaIs with no schistosome infection were examined. Of the 20 acute patients, 15 (75%) had IgA antibodies, whereas only one of the 20 in the chronic stage was positive for IgA. IgM antibodies were detected in 19 of the acute patients and in 17 of the chronic ones (90% positivity). No positive reaction was observed among non-schistosomiasis patients.